ETHICAL ASPECTS OF THE LIFE OF ORPHANS AND CHILDREN LEFT WITHOUT PARENTAL CARE - N. Legkonogikh, Aleksandr; I. Basina, Natalya; N. Mezinova, Galina; B. Smirnova, Svetlana; N. Guz, Aleksey (Revista Inclusiones, 2021)
The perception of new living conditions for orphans and children left without parental care is a complex ethical, psychological and social issue that is relevant in the aspect of children's adaptation to society and coexistence in it. Regulated isolation from society within a separate social conglomerate, subsequently has a negative impact on the formation of the individual, on entering into other rules of life. The article discusses the current vision of this problem, in particular, the ethical aspect of adaptation of orphans and children left without parental care in their independent life, as well as research by domestic and foreign scientists on this issue. Based on the results of an empirical study of the author's community, a strategic construct for working with graduates of orphanages has been developed, with the help of which teachers-psychologists and/or psychologists can develop individual life skills for each individual in this social sector, which will allow a teenager to enter society while preserving his sovereignty, gain skills for their own, independent life management and favorable development of their life.